Comparative study of accelerated ponseti method versus standard ponseti method for the treatment of idiopathic clubfoot - Mahendra Solanki; Anand Ajmera; Sanjay Rawat (Journal of Orthopedics, Traumatology and Rehabilitation, 2018)
Introduction: Clubfoot is a common congenital deformity with incidence of one in thousand live births. Ponseti method is currently the gold standard for treatment of clubfoot which conventionally involves weekly plaster changes. A prospective comparative study was carried out at our institute where we compared one group with weekly plaster change to other group with triweekly plaster change using the classical Ponseti protocol of manipulation. Methods: A total of 40 feet, divided into two groups, were randomly allocated to either Group A – 20 feet (standard Ponseti) or Group B – 20 feet (accelerated Ponseti). Group A underwent serial manipulations and casting once a week and Group B received manipulations and castings thrice a week. Pirani score was documented at presentation, at each cast, and at the time of removal of final cast to assess the success of treatment in terms of Pirani score ≤1. Results: The average number of casts needed for correction in accelerated group was 7 (16 patients, 20 feet) and in standard group was 6.35 (15 patients, 20 feet). The mean follow-up in accelerated group was 7.84 months whereas in standard group was 6.66 months. Tendoachilles tenotomy was required in 65% feet in accelerated group and 55% in standard group. Conclusion: Both methods standard and accelerated Ponseti have proven to be equally efficacious for the management of clubfoot in our study. However, the accelerated method has a overall shorter treatment duration making it more cost effective and convenient for the parents. As patient is under direct observation of surgeons, any complications are detected early and easily. Overall, the accelerated technique is more practical, beneficial, and labor-saving for poor patients from rural part of India where recurrent visit to tertiary government care center is inconvenient and troublesome.